Getting your way every day : mastering the lost art of pure persuasion - Axelrod, Alan, 1952- (AMACOM, 2007)
Classical rhetoric is the most powerful system of persuasion, perfected by the likes of Aristotle, Plato, and Socrates. While the discipline may not sound sexy, its timeless principles really work. Pure persuasion at its best, rhetoric has been long forgotten -- ignored in favor of manipulative tricks masquerading as influence. Getting Your Way Every Day will change that. Author Alan Axelrod offers a new take on the classic strategies -- modernizing them and making them relevant to any business or social situation.